Flipping the Undergraduate Classroom to Develop Student Analytical Thinking Skills - Nattawut Phurikultong; Thiyaporn Kantathanawat (Emerging Science Journal, 2022)
In Thailand, analytical thinking skills (ATS) have been identified as an essential element in the development of a 21st-century workforce. Moreover, due to the Covid-19 pandemic and the concern for student health and safety, the Thai Ministry of Education has stated that online education will become part of the New Normal in education. Therefore, it has become imperative that the most effective methods and mechanisms be found for online teaching in Thailand. Therefore, the authors investigated which factors increase Thai student ATS by flipping the classroom environment and using digital storytelling and inquiry-based learning (IBL). Therefore, this research aims to develop and evaluate the LIFD ATS instruction model to study the proposed effects of the ATS instruction model. A mixed research methodology was employed. The mean, standard deviation, and t-test were used to analyze the data. From the qualitative review, an initial learning model was developed and subsequently examined by a panel of eight education experts. After that, 40 students became the study's experimental group for the revised model. The results showed that the results of the expert assessment of the learning environment model using a flipped classroom combined with IBL and digital storytelling to promote ATS and academic achievement had appropriateness at the highest level. The evaluation of the student results using the ATS model identified four significant results. These were: 1) Post-test after the student's use of the ATS model determined their ATS abilities were higher than before the class. 2) Student learning achievement, innovation, and ICT skills increased as an outcome of the ATS model’s use. 3) The comparison of academic achievement after study of the students who studied with the format was 83.33%, higher than the specified 80% criteria and previously established assumptions. 4) The evaluation results of the model’s effectiveness determined that the learning effectiveness index (EI) of the learners was 0.6666 and the EI of the ATS was 0.6966, which was higher than 0.50, thus meeting the specified criteria. The study contributes to the knowledge concerning student ATS and these skills’ importance to a 21st century knowledge worker. Doi: 10.28991/ESJ-2022-06-04-06 Full Text: PDF